Strategy Development of CV. GAMMA CiTRA MANDIRI (KAOSPOLOS) in Order to Increase Customer and Profit (The Indonesian Journal of Business Administration, 2013)
The study aims to develop business strategy that can support KaosPolos in getting the customer and growing a business is run, so that the profit earned can also be increased, Study conducted in 2013 at KaosPolos that located in South Tangerang city. The authors propose the business strategy using tools as Generic Competitive Strategy, Business Model Canvas, and Business Diamond Strategy. the implementation of business solutions is divided into two programs, which is short-term and long-term program program. so as to implement a given strategy will improve customer and profit.Â Keywords: Clothing, Business Model Development, Diamond Strategy, increase performance